2001
DOI: 10.1097/00003643-200108000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lidocaine on neutrophil respiratory burst during induction of general anaesthesia and tracheal intubation

Abstract: Background and objective Respiratory burst is an essential component of the neutrophil's biocidal function. In vitro, sodium thiopental, iso¯urane and lidocaine each inhibit neutrophil respiratory burst. The objectives of this study were (a) to determine the effect of a standard clinical induction/tracheal intubation sequence on neutrophil respiratory burst and (b) to determine the effect of intravenous lidocaine administration during induction of anaesthesia on neutrophil respiratory burst. Methods Twenty ASA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In the present study, cells that showed high-intensity fluorescence (rho+) accounted for 5-7% of unstimulated neutrophils; this proportion corresponds to previous reports (32). Higher baseline ROS production in unstimulated rho+ neutrophils from cord blood, in line with other data, could reflect their higher responsiveness to upregulation of mediators of systemic inflammation, which is also a typical physiological feature of labor (33,34). It could be supposed that circulating rho+ neutrophils represent the first line of defense, but their precise role remains unclear.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, cells that showed high-intensity fluorescence (rho+) accounted for 5-7% of unstimulated neutrophils; this proportion corresponds to previous reports (32). Higher baseline ROS production in unstimulated rho+ neutrophils from cord blood, in line with other data, could reflect their higher responsiveness to upregulation of mediators of systemic inflammation, which is also a typical physiological feature of labor (33,34). It could be supposed that circulating rho+ neutrophils represent the first line of defense, but their precise role remains unclear.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, under clinical conditions, lidocaine was demonstrated to counteract the decrease in neutrophil respiratory burst during induction of anesthesia (34). Moreover, lidocaine is able to decrease cellular cAMP inversely associated with NOX activity via purinergic receptors and Gαi proteins (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…One clinical study examining neutrophils taken from lidocaine-treated patients detected significantly reduced superoxide anion release compared to patients who didn't receive lidocaine (166). Contrary to this finding, a clinical trial studying bolus lidocaine (1.5 mg.kg -1 ) administered at induction of anaesthesia found that lidocaine actually preserved neutrophil respiratory burst compared to neutrophils from control patients who received saline (167).…”
Section: Effects On Immune Cellsmentioning
confidence: 75%
“…Attenuation of the hemodynamic response can be beneficial and prevent complications, especially in those with coronary ischemic disease 9 . When systemic lidocaine is used it decreases airways reactivity being useful in patients with asthma [10][11][12] , it decreases intraoperative anesthetic consumption 13,14 , the blockade of the systemic inflammatory response secondary to surgery 15,16 , postoperative pain 13,14,17 , and favors early hospital discharge 18 .…”
Section: Introductionmentioning
confidence: 99%